THE PRIMARY CAUSES OF RISK EMERGENCE IN SMALL BUSINESSES - Ismoilova Zebiniso Sarvarbek qizi (TADQIQOTLAR, 2026)
Abstract. This paper explores the primary causes of risk emergence in small businesses. Due to their limited resources and heightened vulnerability to external factors, small enterprises are particularly susceptible to various risks that can hinder their stability and growth. The study identifies key factors contributing to risk emergence, including economic instability, lack of financial and human resources, insufficient strategic planning, low adaptability to market changes, and regulatory or legal uncertainties. Understanding and categorizing these risk factors can help develop effective risk management strategies to enhance the resilience and long-term viability of small businesses.